2016
DOI: 10.1159/000449220
|View full text |Cite
|
Sign up to set email alerts
|

How Many for Lunch Today? Seasonal Fission-Fusion Dynamics as a Feeding Strategy in Wild Red-Capped Mangabeys (Cercocebus torquatus)

Abstract: For group-living primates, social organization hinges upon multiple factors, including group size, group cohesion, and the group's age and sex composition. Fission-fusion dynamics reduce the risks of living in a large group, which can include feeding competition related to the seasonality of resources. Here we report on the group dynamics (i.e. formation of parties) of a population of red-capped mangabeys (Cercocebus torquatus) located in Sentier Nature forest, South Loango National Park, Gabon, and examine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 46 publications
2
6
0
Order By: Relevance
“…Many species alter their behavior in response to changing resource availability (Candolin & Wong, 2012) and our results show that C. a. ruwenzorii is no exception. Similar to studies done on other primates ( Cercocebus torquatus, Dolado et al., 2016; Rhinopithecus bieti, Ren et al., 2012; Papio hamadryas , Schreier & Swedell, 2012b; Pongo pygmaeus, Sugardjito et al., 1987) and nonprimates ( Orcinus orca, Foster et al., 2012; Loxodonta africana , Wittemyer et al., 2005), we found that C. a. ruwenzorii units increase their association levels during times of peak food availability. Food competition decreases when resources are abundant, allowing animals to aggregate if they choose, which allows them to take advantage of the benefits that large groups have for predator avoidance (Hamilton, 1971; Sueur et al., 2011).…”
Section: Discussionsupporting
confidence: 89%
“…Many species alter their behavior in response to changing resource availability (Candolin & Wong, 2012) and our results show that C. a. ruwenzorii is no exception. Similar to studies done on other primates ( Cercocebus torquatus, Dolado et al., 2016; Rhinopithecus bieti, Ren et al., 2012; Papio hamadryas , Schreier & Swedell, 2012b; Pongo pygmaeus, Sugardjito et al., 1987) and nonprimates ( Orcinus orca, Foster et al., 2012; Loxodonta africana , Wittemyer et al., 2005), we found that C. a. ruwenzorii units increase their association levels during times of peak food availability. Food competition decreases when resources are abundant, allowing animals to aggregate if they choose, which allows them to take advantage of the benefits that large groups have for predator avoidance (Hamilton, 1971; Sueur et al., 2011).…”
Section: Discussionsupporting
confidence: 89%
“…a. ruwenzorii is no exception. Similar to studies done on other primates (Cercocebus torquatus, Dolado, Cooke, & Beltran, 2016;Rhinopithecus bieti, Ren, Li, Garber, & Li, 2012;Papio hamadryas , Schreier & Swedell, 2012b;Pongo pygmaeus, Sugardjito, Te Boekhorst, & van Hooff, 1987) and non-primates (Orcinus orca, Foster et al, 2012;Loxodonta africana , Wittemyer et al, 2005), we found that C. a. ruwenzorii units increase their association levels during times of peak food availability. Food competition decreases when resources are abundant, allowing animals to aggregate if they choose, which provides benefits for predator avoidance (Hamilton, 1971;Sueur et al, 2011).…”
Section: Discussionsupporting
confidence: 89%
“…While the vast majority of primate fission-fusion literature has traditionally focused on chimpanzees and spider monkeys, there is growing evidence that fission-fusion dynamics are, in fact, more common than previously recognized (e.g., [Aureli et al, 2008]), and that the demographic, ecological, and social variables described above can be applied more broadly to explain fission-fusion dynamics across the primate order. For instance, in many nonhuman primates, group fissions and concomitant changes in ranging behavior commonly occur within a feeding context (e.g., [Dolado et al, 2016; Dolado et al, 2017; Izar et al, 2012; Ren et al, 2012] and/or in accordance with social variables such as subgroup size or the presence of mates (e.g., [Ellis, and Di Fiore, 2019; Dias, and Strier, 2003; Strier, 2018]. Here, we add to this growing body of literature by quantifying patterns of range use and overlap in a strepsirrhine with high fission-fusion dynamics, the black-and-white ruffed lemur ( Varecia variegata ) [Baden et al, 2016].…”
Section: Introductionmentioning
confidence: 99%